Managing complexity: a problem of chaos in fisheries policy - Filipe, J. A. C. B. (2020)
This work intends to present chaos theory (and dynamical systems such as the theories of complexity), in terms of interpretation of ecological phenomena. The chaos theory applied in the context of ecological systems, especially in the context of fisheries has allowed the recognition of the relevance of this kind of theories to explain fishing phenomena and fisheries policies. It has permitted new advances in the study of marine systems, contributing to the preservation of fish stocks. This paper deals with the way how to manage fisheries taking chaos in account of the problem.